Reconstitution of a minimal mtDNA replisome in vitro - Korhonen, Jenny A (Nature Publishing Group, 2004)
We here reconstitute a minimal mammalian mitochondrial DNA (mtDNA) replisome in vitro. The mtDNA polymerase (POLγ) cannot use double-stranded DNA (dsDNA) as template for DNA synthesis. Similarly, the TWINKLE DNA helicase is unable to unwind longer stretches of dsDNA. In combination, POLγ and TWINKLE form a processive replication machinery, which can use dsDNA as template to synthesize single-stranded DNA (ssDNA) molecules of about 2 kb. The addition of the mitochondrial ssDNA-binding protein stimulates the reaction further, generating DNA products of about 16 kb, the size of the mammalian mtDNA molecule. The observed DNA synthesis rate is 180 base pairs (bp)/min, corresponding closely to the previously calculated value of 270 bp/min for in vivo DNA replication. Our findings provide the first biochemical evidence that TWINKLE is the helicase at the mitochondrial DNA replication fork. Furthermore, mutations in TWINKLE and POLγ cause autosomal dominant progressive external ophthalmoplegia (adPEO), a disorder associated with deletions in mitochondrial DNA. The functional interactions between TWINKLE and POLγ thus explain why mutations in these two proteins cause an identical syndrome.